Virtualitas Retrokognisi-Magi Om Hao “Kisah Tanah Jawa” di Media Sosial - Abd. Aziz Faiz (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Virtualization enables the magical to be imagined and seen through social media. Om Hao and the crew from Kisah Tanah Jawa (the Tale of the Land of Java) can make retrocognition-magic as a show by using a realist narrative that allows viewers to have the sensation of an unseen 'presence'. Therefore, this paper aims to explore Om Hao's retrocognition-magic virtualization and the narratives that operate within it. To complete this objective, the netnographic method was used in the form of online observation and videography on Kisah Tanah Jawa youtube. This study has resulted that: first, retrocognition virtuality is performed through new media technology devices that are able to visualize event actors and bring them closer and real to their viewers; Second, Om Hao's retrocognition-magic virtuality becomes extra textual which builds the interaction between the magic and the actual in social media where both of them become the power of the narrative that contains the magic appearing and thought of; third, Virtuality magic appears actual because it is supported by Om Hao's narrative that sounds rational, objective and neutral. All the three are strengthened because they are relevant to the historical experience, stories, and mystical beliefs of the Javanese people as a socio-cultural context. As a product of postmodern culture, Om Hao's retrocognition-magic virtualization is seemingly able to present a divergent fantasy of alternative